Використання інноваційних методів навчання у підготовці фахівців дошкільного профілю - Смолюк, Іван; Солодуха, Юлія; Ясінська, Наталія (Східноєвропейський національний університет імені Лесі Українки, 2017)
У статті йдеться про використання інноваційних методів навчання у підготовці майбутніх педагогів, які будуть працювати з дітьми дошкільного віку. Зокрема, висвітлено теоретичні засади інтерактивного навчання; узагальнено теоретичний досвід використання інтерактивних методів у підготовці фахівців дошкільного профілю. The article deals with the using of innovative teaching methods in the preparation of future specialists who will work with children of preschool age. In particular, the theoretical basis of interactive learning is highlighted; General theoretical experience of using of interactive methods in training of preschoolers. The article deals with modern interactive forms of work with students. Undoubtedly, other practice forms of work are used in the practice of pedagogical schools, colleges, institutes, universities that train future pedagogues-preschoolers. However, the purpose of this publication was not to list all existing interactive forms, but to draw attention to the most effective forms of work for the training of preschoolers.Key words: informational methods of teaching, personal activity, human technologies.
Keywords: iннoвaцiйнi методи навчання; iннoвaцiйнa дiяльнiсть; iннoвaцiйнi технології